Protection status assessment, prospects and methods of conservation of species of Schivereckia (Draba s. l.; Brassicaceae) in Ukraine - Kagalo, A.; Kolodiy, V.; Lyubinska, L. (Український ботанічний журнал, 2018)
On the basis of generalization of long-term research data on the status of populations and habitats of taxa of Schivereckia Andrz. ex Besser (Draba L. s. l.; Brassicaceae), S. podolica and S. mutabilis (= S. podolica s. l.) in Ukraine, the assessment of their conservation status and state and the recommended optimal modes for their conservation are provided. It has been shown that populations of these taxa are negatively affected by both anthropogenic and natural factors. Anthropogenic factors include pollution by household waste, sewage drains, grazing, trampling, burning, explosive works, mechanical destruction of ecotopes through the extraction of limestone or gravel. Natural factors are cenotic (reduction of competitiveness), biological (declining vitality of populations), physical (water erosion and natural degradation of slopes due to weathering of rocks), and climatic (influence of wind) ones. It is shown that, despite the fact that species of this genus are not directly harvested or destroyed by humans, their populations are indirectly influenced by negative anthropogenic and natural factors listed above. This negatively affects the vitality and viability of its local populations and cenopopulations. In this regard, it is expedient to transfer this species from the category Not Evaluated (currently applied in the Red Data Book of Ukraine) to the category Vulnerable. For further optimization of preservation of this species complex in various localities and habitats, it is advisable to develop appropriate nature conservation management plans, for Podilski Tovtry NNP as an example. Within the framework of such management plans it is advisable to take into account both scientific and administrative actions for species protection, as well as impact of environmental education and possibility of cultivation. На підставі узагальнення матеріалів багаторічних досліджень стану популяцій та оселищ видів роду Schivereckia (Brassicaceae) – Schivereckia podolica та S. mutabilis (= S. podolica s. l.) в Україні дана оцінка їхнього стану й охоронного статусу та рекомендовані оптимальні шляхи збереження. Показано, що популяції виду зазнають негативного впливу як антропогенних (засмічення екотопів побутовим сміттям, заливання каналізаційними стоками, випасання, витоптування, випалювання, вибухові роботи, механічне руйнування екотопів внаслідок видобування вапняку, щебеню), так і природних (ценотичних (зменшення конкурентної здатності), біологічних (зменшення життєвості популяції), фізичних (водна ерозія та природне руйнування схилів у процесі вивітрювання порід), кліматичних (вплив вітру) чинників. Показано, що, незважаючи на те, що види роду не знищуються людиною, їхні популяції зазнають опосередкованого впливу негативних для виду антропогенних і природних чинників, які негативно впливають на життєздатність локальних ценопопуляцій. У зв'язку із цим, доцільно перевести видовий комплекс з категорії "неоцінений" у Червоній книзі України до категорії "вразливий". Для подальшої оптимізації збереження цього видового комплексу в різних локалітетах і оселищах доцільно розробити відповідні природоохоронні менеджмент-плани за прикладом НПП "Подільські Товтри". У рамках таких менеджмент-планів слід урахувати наукові, організаційно-природоохоронні, еколого-просвітницькі та інтродукційні заходи. На основании обобщения материалов многолетних исследований состояния популяций и местообитаний видов рода Schivereckia (Brassicaceae) – Schivereckia podoliса и S. mutabilis (= S. podolica s. l.) в Украине даны оценка их состояния, охранного статуса и рекомендации для оптимального сохранения. Показано, что популяции вида испытывают негативное влияние как антропогенных (засорение экотопов бытовым мусором, заливка канализационными стоками, выпас, вытаптывание, выжигание, взрывные работы, механическое разрушение экотопов вследствие добычи известняка, щебня), так и естественных (ценотических (уменьшение конкурентной способности), биологических (уменьшение жизненности популяции), физических (водная эрозия и естественное разрушение склонов в процессе выветривания пород), климатических (влияние ветра) факторов. Показано, что, несмотря на то, что виды рода не уничтожаются человеком, их популяции испытывают опосредованное влияние негативных для вида антропогенных и природных факторов, что влияет на жизнеспособность локальных ценопопуляций. В связи с этим, целесообразно перевести этот видовой комплекс из категории "неоцененный" в Красной книге Украины в категорию "уязвимый". Для дальнейшей оптимизации сохранения этого видового комплекса в различных локалитетах и местообитаниях целесообразно разработать соответствующие природоохранные менеджмент-планы по примеру НПП "Подольские Товтры". В рамках таких менеджмент-планов следует учесть научные, организационно-природоохранные, эколого-просветительские и интродукционные мероприятия.